Genetic control of frost tolerance in Pinus patula × Pinus tecunumanii (LE and HE) hybrid families - Malinga, Sithembile (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScFor)--Stellenbosch University, 2018.